Role of Information Security Policy in Providing Information Security in Economic Fields - Majidova Mohigul (Zien Journals, 2022)
In this article, the security policy in the economic sectors and the scheme of information flow in the provision of security, the extent to which the business process provides the information flow, and the additional measures that should be applied to ensure that the provision of information protection is important and viable. Shows all fields.
Keywords: Information security policy; information flow scheme; security policy rules; computer viruses